Evaluation of Drive-Thru Services Using Logic Model: A Study of Motor Vehicle Taxpayers in Buleleng, Bali - Sangging, Wayan Devin Amabel; Suwena, Kadek Rai; Suarmanayasa, I Nengah (Yayasan Sembilan Pemuda Indonesia, 2025)
This study systematically evaluates the impact of drive-thru services on taxpayer satisfaction and compliance at the Buleleng Tax Office, Bali, addressing a critical gap in public service assessment literature. Employing the Logic Model framework (inputs, activities, outputs, outcomes), we collected data from 61 purposively sampled drive-thru service users through structured questionnaires and in-depth interviews. Analysis revealed consistently higher satisfaction levels, with positive response differentials (F+ - F-) ranging from +5% to +21.4% across all components. The Activity component showed the most significant positive disparity (+21.4%), indicating particularly strong approval of service delivery processes. This research presents the first empirical application of the Logic Model to assess drive-thru tax services, introducing a structured evaluation approach for mobile government service innovations. Findings suggest that while drive-thru services enhance satisfaction, sustained improvements in physical infrastructure (Inputs) and outcome monitoring are needed to maintain trust and compliance long-term. The study provides tax authorities with a replicable evaluation framework and evidence-based insights for optimizing mobile service delivery models to improve taxpayer experiences.